Modeling the Disintegration Process in Anaerobic Digestion of Tannery Sludge and Fleshing - Polizzi, Cecilia; Alatriste-Mondragón, Felipe; Munz, Giulio (Frontiers in Environmental Science, 2017)
Mathematical modelling of anaerobic digestion is widely acknowledged as a powerful tool to improve the understanding of the process and to support full-scale plant design, operation and optimization. In this work, a modified version of the IWA-ADM1 model is proposed to simulate the anaerobic digestion of tannery primary sludge and fleshing, with special emphasis on the disintegration formulation. Multiple batch tests were performed at different inoculum/substrate VS-mass ratio, in order to evaluate the biodegradability of the two substrates and to provide experimental data for modelling purposes. Beside the necessary adjustments of substrates’ COD fractionation, the structure modifications of the model focused on the disintegration and hydrolysis. The Contois Monod-based model was adopted to describe disintegration kinetics and the results were compared to the traditionally adopted first-order kinetic. The fate of particulate matter generated from biomass lysis was also questioned and a new model variable was introduced to account for cellular lysis products. Finally, a further modification differentiated substrate particulate matter into a readily and a slowly hydrolysable fraction. Batch tests confirmed that tannery primary sludge and fleshing are suitable substrates for anaerobic digestion, exhibiting specific methane productions of: 0.26±0.06 and 0.47±0.05 Nm3Kg-1VS, respectively. Modelling results showed that the proposed modifications were crucial for successful simulation of experimental data referring to fleshing, whereas did not have a significant effect on the results related to primary sludge degradation. This work is the first application of an IWA-ADM1-based model to anaerobic digestion of tannery waste.